Development of LEKER SIRA E-LKPD on Nganggung Tradition to Enhance Learning Outcomes and Religious Values in Class X Social Studies at SMA 1 Pemali - Sulistia, Sulistia; Widiadi, Aditya Nugroho; Agung, Dewa Agung Gede (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
In the process of learning in schools, teachers, students, media, and the environment form a complex interplay. The role of teachers becomes more challenging as students heavily rely on them, leading to ineffective learning. Due to this dependence, a solution can be found by utilizing instructional materials that help teachers facilitate independent learning for students. This research aims to produce